2017
DOI: 10.17219/acem/62536
|View full text |Cite
|
Sign up to set email alerts
|

An animal model of the procognitive properties of cysteine protease inhibitor and immunomodulatory peptides based on colostrum.

Abstract: Background. The positive effect of human cystatin C on the development of Alzheimer's disease has been reported, as it inhibits the formation of β-amyloid oligomers and amyloidogenesis. Cystatin C has been found to have a neuroprotective effect by inhibiting cysteine proteases, inducing autophagy and neurogenesis. There is a growing interest in the procognitive properties of colostrum-based specimens, which could delay dementia and ameliorate memory deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Previous research conducted with the use of ovocystatin in animal models revealed that its oral intake correlated with improved cognitive functions assessed with the Morris water maze. Interestingly, these effects were also observed in young rats [ 112 ]. Similar results were obtained in the animal model of B6C3-Tg transgenic mice used for the recreation of Alzheimer’s disease pathology.…”
Section: Cystatin Cmentioning
confidence: 88%
“…Previous research conducted with the use of ovocystatin in animal models revealed that its oral intake correlated with improved cognitive functions assessed with the Morris water maze. Interestingly, these effects were also observed in young rats [ 112 ]. Similar results were obtained in the animal model of B6C3-Tg transgenic mice used for the recreation of Alzheimer’s disease pathology.…”
Section: Cystatin Cmentioning
confidence: 88%
“…It has been shown up until now, that ovocystatin has a beneficial impact on cognitive function in young rats, and might prevent aging-related cognitive impairment in older animals [ 21 ] and reduce memory decline in APP/PS1 mice model [ 23 , 24 ]. However, its potential molecular mechanism of action is not explained and needs to be examined in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, bioactive peptides/proteins are promising candidates for use as the inhibitors of Aβ fibril formation, such as ovocystatin (ovoC). Interestingly, ovocystatin improves cognitive function in young rats [ 21 ] and prevents aging-related cognitive impairment in older animals [ 22 ]. Moreover, recently published studies showed that the administration of ovoC in drinking water might be effective in the prevention of cognitive deterioration in APP/PS1 mice [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 BC or its formulations have pleiotropic properties that could be useful in individuals with a decline in cognitive functions, which include antioxidant, anti-inflammatory, cellular survival, and inhibition of Aβ-fibril aggregation. [5][6][7][8][9][10] Several studies have shown that reactive oxygen species, neuroinflammation, and senescent cells are involved in the pathogenesis of impairment of cognitive function. 11 Colostrum was investigated in a small number of clinical studies, and the authors reported the beneficial effect of using colostrum in mild-moderate impairment of cognitive functions in Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%